The capital structure of multinational corporations: Canadian versus U.S. evidence - Mittoo, Usha R.; Zhang, Zhou (Journal of Corporate Finance, 2008)
Contrary to the U.S. evidence, we show that Canadian multinational corporations (MNCs) display higher leverage than domestic firms (DCs). This higher leverage is due to lower agency costs of debt associated with MNCs' U.S. operations. We also find that the Canadian firms with international bond market access have higher leverage than firms without such access. Comparison with a U.S. matched sample shows that the sensitivity of leverage to firm-specific factors differs between the two countries, especially for the MNCs samples. Our evidence indicates that capital structures of MNCs are a complex interaction of both home and host country factors and differences in leverage determinants across countries.